Association between dietary diversity and healthy aging: a systematic review - Roghayeh Molani-Gol; Maryam Rafraf; Beitullah Alipour (BMC Nutrition)
Abstract Objective The proportion of older people has been enhanced in the past half-century around the world, consequently leading to the increasing overall prevalence of age-related health conditions. The present study aims to summarize the current evidence regarding the association between dietary diversity (DD) and the components of healthy aging. Methods The databases, including Scopus, PubMed, Web of Science, and Google Scholar, were searched using relevant keywords and without date restrictions up to November 2023. All original articles written in English evaluating the association between DD and healthy aging components were eligible for this systematic review. Results Totally, 2728 records were obtained in electronic search databases after removing duplicates and irrelevant studies based on the title and abstract; the full text of the 64 articles was critically screened, and 32 cross-sectional studies and 17 cohort studies were included in this review. Except for two cases, all of these studies (95.9%) reported that high DD was associated with lower cognitive and physical frailties, low sleep disturbance and mental disorders, and good nutritional status among the elderly population. Conclusion Findings suggest higher DD may contribute to healthy aging through improved nutrient intake and reduced risk of age-related diseases, but heterogeneity in study designs limits conclusive evidence. Enhancing healthy dietary behaviors for older people is suggested to increase their awareness and consequently DD. Further research is needed to confirm these results and the causal relationship.